Prevalence of obesity and factors contributes to obese among medical student in Medical Faculty of Udayana University in 2016 - Shenbagam Mahalingam; Desak Wihandani (Intisari Sains Medis, 2018)
Background: Obesity is a medical condition in which excess body fat has accumulated to the extent that is may have a negative effect on health. The increased prevalence has been in the developed country and also in developing country.Methods: This is crossectional-descriptive research. 67 samples that met inclusion criteria were included in the research. Samples obtained using consecutive sampling technique. The sample divided into four categories; underweight, normal weight, overweight, and obeseResults: 26.9% were overweight, and 10.4% were obese with a total of 67 samples. Most of the sample who met obese criteria are male.Conclusions: Prevalence of obesity among medical students in Udayana University with results 26.9% overweight and 10.4% obesity out of 67 samples, meanwhile 47,8% represent normal weight, and 14.9% represent underweight. In the inactive category, there are 42 adolescents (62.7%) out of 67 samples. Only 25 (37.3%) out of 67 samples were active physically.